Long-term survival of 2997 finger metacarpophalanageal joint arthroplasties from the Norwegian Arthroplasty Register. (January 2023) - Brendsdal, Eirik S.; Lie, Stein A.; Furnes, Ove; Hove, Leiv M.; Krukhaug, Yngvar
We present the long-time survival of 2997 primary metacarpophalangeal (MCP) joint implants from the Norwegian Arthroplasty Register from 1994 to 2019. Six different implants were compared in terms of survival and risk of revision. The majority of implants were inserted in patients diagnosed with inflammatory diseases and in women. The overall survival was found to be 94%, 89%, 85% and 84% after 5, 10, 15 and 20 years. The most prevalent reason for revision was a fractured prosthetic component, and the second was pain. Implants inserted in the right hand and in younger patients had a higher risk for revision. Sex, type of implant, finger treated, one- or two-component prosthesis, and inflammatory or non-inflammatory conditions did not influence the survival. The frequency of MCP joint implantations decreased during the observation period. Our data show satisfactory long-term survival of the MCP implants, with no difference found between implant types or concepts. Level of evidence: II